The Existence of Solutions for Four-Point Coupled Boundary Value Problems of Fractional Differential Equations at Resonance - Yumei Zou; Lishan Liu; Yujun Cui (Abstract and Applied Analysis)
A four-point coupled boundary value problem of fractional differential equations is studied. Based on Mawhin’s coincidence degree theory, some existence theorems are obtained in the case of resonance.